Management and outcome across the spectrum of high‐risk patients with myocardial infarction according to the thrmobolysis in myocardial infarction (TIMI) risk‐score for secondary prevention. Issue 11 (1st September 2021) - Grinberg, Tzlil; Bental, Tamir; Hammer, Yoav; Assali, Abid; Vaknin‐Assa, Hana; Wiessman, Maya; Perl, Leor; Kornowski, Ran; Eisen, Alon
Abstract: Background: Patients with myocardial infarction (MI) are at increased risk for recurrent cardiovascular events, yet some patients, such as the elderly and those with prior comorbidities, are particularly at the highest risk. Whether these patients benefit from contemporary management is not fully elucidated. Methods: Included were consecutive patients with MI who underwent percutaneous coronary intervention (PCI) in a large tertiary medical center. Patients were stratified according to the thrombolysis in myocardial infarction (TIMI) risk score for secondary prevention (TRS2°P) to high (TRS2°P = 3), very high (TRS2°P = 4), or extremely high‐risk (TRS2°P = 5–9). Excluded were low and intermediate‐risk patients (TRS2°P < 3). Outcomes included 30‐day/1‐year major adverse cardiac events (MACE) and 1‐year mortality. Temporal trends were examined in the early (2004–2010) and late (2011–2016) time‐periods. Results: Among 2053 patients, 50% were high‐risk, 30% very high‐risk and 20% extremely high‐risk. Extremely high‐risk patients were older (age 74 ± 10 year) and had significant comorbidities (chronic kidney disease 68%, prior CABG 40%, heart failure 78%, peripheral artery disease 29%). Drug‐eluting stents and potent antiplatelets were more commonly used over time in all risk‐strata. Over time, 30‐day MACE rates have decreased, mainly attributed to the very high (11.3% to 5.1%, p = .006) and extremely high‐risk groups (15.9% to 8.0%, p = .016), but not the high‐risk group, with similar quantitative results for 1‐year MACE. The rates of 1‐year mortality remained unchanged in either group. Conclusion: Within a particularly high‐risk cohort of MI patients who underwent PCI, the implementation of guideline‐recommended therapies has improved over time, with the highest‐risk groups demonstrating the greatest benefit in outcomes.